Modulatory effects of endothelin on baroreflex activation in the nucleus of the solitary tract - Mosqueda-Garcia, Rogelio; Appalsamy, Martin; Fernandez-Violante, Roxana; Hamakubo, Takao (European journal of pharmacology, 1998)
In this study, we determine the effects of endogenous endothelin on baroreflex activation. After control baroreflex slopes were obtained, the animals received bilateral intra-nucleus tractus solitarii microinjections of saline, or equimolar doses (4 pmol/60 nl) of the endothelin ET A receptor antagonist cyclo ( d-Trp- d-Asp-Pro-Val-Leu (BQ-123), Homopiperinidinyl-CO-Leu- d-Trp(CHO)- d-Trp-OH (BQ-610), or the endothelin ET B receptor antagonist N- cis-2,6-dimethylpiperidinocarbonyl- l- γ-MeLeu- d-Trp(COOCH 3)- d-Nle (BQ-788). Intra-nucleus tractus solitarii administration of BQ-123 resulted in a brief initial pressor effect followed by hypotension which resolved by 15 min. The baroreflex slope was significantly enhanced when tested 15 min after BQ-123 treatment (from 2.4±0.5 ms/mmHg to 3.5±0.4 ms/mmHg). Similar effects were observed with the other endothelin ET A receptor antagonist, except that the hypertensive and hypotensive responses were more pronounced while the baroreflex slope was similarly increased. In contrast, the endothelin ET B receptor antagonist did not evoke appreciable changes in hemodynamics or in baroreflex slopes. Our results support the concept that endothelin prominently affects reflex cardiovascular function through the endothelin ET A receptor subtype.